The Brogyntyn Lute Book - Spencer, Robert 1932-1997; Alexander, Jeffrey; Rastall, Richard (Kilkenny Boethius Press, 1978)
The Brogyntyn I.27 manuscript is part of the collection of manuscripts from the Brogyntyn Library near Oswestry deposited at the Library in 1934. It contains music for the lute copied about 1595, and transcripts of poems, elegies and legal miscellanea by the lawyer-poet Thomas Tanat (1603-69) of Broxton, Cheshire, added between about 1621 and 1629.
Keywords: 16th Century (1501-1600); 17th Century (1601-1700); Lute; Duet; United Kingdom